SELF-OTHER DIALECTIC, HEGEL, AND THE CONTEMPORARY THEORY OF ’THE POLITICS OF RECOGNITION’ - Gedifew, Belayneh Taye (Skhid, 2020)
This paper approached the concepts of self-other dialectic and "the politics of recognition" from the aspect of Hegel’s self-consciousness chapter in the Phenomenology of Spirit. Various authors attribute Hegel as a source and inspiration for the current theories of identity politics. This article is, therefore, focused on examining the implication of Hegel’s idea of ’recognition’ and ’self-consciousness’ on the contemporary debates of identity politics. Hegel has an enormous contribution to the current debate on identity politics. This article shows that with specific reference to the Phenomenology of Spirit, Hegel’s understanding of ’recognition’ in terms of the dialectic of consciousness is vital to see the contemporary theory of the politics of recognition in a broader epistemological and ontological basis. When it comes to the more practical and empirical political situation of these days, his idea of freedom and recognition has many important insights that support constitutional liberal system to handle ’needs’ and ’demands’ of recognition raised in identity politics. As Hegel has emphasised in many of his works, in the progress of human history, state (including the established institutions) is the Absolute Spirit that actualises the reciprocal freedom and mutual recognition of individuals in a broader political space. Based on these Hegelian insights, the study concluded that education, deliberative democracy, and institutions are substantial to handle competing ’needs’ and ’demands’ of recognition in identity politics without granting group rights and interests a constitutional recognition.